Quality of life in children with chronic disease in Malang city assessed using pediatric quality of life inventoryTM - Yaalmolly Vinothini Ravindran; Irfan Agus Salim; Haryudi Aji Cahyono (Pediatric Sciences Journal, 2022)
Introduction: A chronic disease is known to be a condition that affects daily function and daily activity which tends to cause someone to be hospitalized. A chronic disease in children triggers several changes in physical, social, emotional, and educational aspects and it can affect the quality of life and development of the child. The purpose of this study is to determine the quality of life of children with chronic disease in Malang city using PedsQLTM. Method: This study is an analytic observational study using a cross-sectional design. Data collection was using purposive (non-probability) sampling with a total sample of 82 respondents. Data collection was carried out using a generic PedsQLTM questionnaire version 4.0 with a google form. Data analysis was performed using Univariate analysis (Descriptive Respondents) and bivariate analysis (Correlation Analysis using Chi-Square). Results: The results showed that the factors that are significantly associated with the quality of life of children are the type of disease and the child's nutritional status (p-value= 0.005; 0.009< Level of Significance = 0.05) while other factors such as age, gender, parents' knowledge, and education background, duration of disease, parents' social and economic condition and several children are not significantly associated with the quality of life. Conclusion: The factors that are significantly associated with the quality of life of children were the type of disease and nutritional status.